2020
DOI: 10.1093/mnras/staa063
|View full text |Cite
|
Sign up to set email alerts
|

The first Doppler imaging of the active binary prototype RS Canum Venaticorum

Abstract: We present the first Doppler images of the prototypical active binary star RS CVn, derived from high-resolution spectra observed in 2004, 2016 and 2017, using three different telescopes and observing sites. We apply the least-squares deconvolution technique to all observed spectra to obtain high signal-to-noise line profiles, which are used to derive the surface images of the active K-type component. Our images show a complex spot pattern on the K star, distributed widely in longitude. All starspots revealed b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The active longitude switches from one hemisphere to the other. Xiang et al (2020) presented the first Doppler images of the active K-type component of the prototypical binary star RS Canum Venaticorum. The maps showed that the spots located below a latitude of about 70°, but distributed widely in longitude.…”
Section: Introductionmentioning
confidence: 99%
“…The active longitude switches from one hemisphere to the other. Xiang et al (2020) presented the first Doppler images of the active K-type component of the prototypical binary star RS Canum Venaticorum. The maps showed that the spots located below a latitude of about 70°, but distributed widely in longitude.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the detailed investigation of the eclipse time variations in Kepler binaries, Balaji et al (2015) found that half of close binaries exhibit asynchronous differential rotations on their component stars. Furthermore, to uncover stellar differential rotation, the Doppler imaging technique (Gu et al 2003;Özdarcan et al 2016;Xiang et al 2020) has been proposed by tracing the spot migration on the stellar surface. However, this technique requires high-resolution and long-term spectroscopic observations, which greatly limit its application over a wide range.…”
Section: Introductionmentioning
confidence: 99%
“…Starspots on binaries with rapidly rotating late-type components are prominent (Holzwarth & Schüssler 2003a,b;Lurie et al 2017), such as RS CVn stars (Gu et al 2003;Xiang et al 2020a) and W UMa stars (Barnes et al 2004;Şenavcı et al 2011). The properties of starspot on binary can be studied from Doppler/Zeeman Doppler images (Gu et al 2003;Xiang et al 2020b) and photometry (Özavcı et al 2018;Pi et al 2019).…”
Section: Introductionmentioning
confidence: 99%